Perda da tolerância à dessecação em sementes de espécies florestais - Fernandes, Alana Chocorosqui (2020)
Threats to biodiversity such as deforestation, fires and climate change have been observed more frequently and intensely in recent years. The ability to tolerate these environmental and human pressures will represent the success or failure of species in the future. Desiccation tolerance is a skill present in orthodox seeds that makes them capable of surviving minimum water levels without accumulating lethal damage, resuming their metabolism after hydration. Loss of desiccation tolerance makes orthodox seeds susceptible to adverse environmental conditions and has been associated with root protrusion. Recent work, however, has shown that loss of desiccation tolerance varies between species and within the same species. Thus, the present study aimed to characterize the loss of desiccation tolerance during the germination of orthodox seeds of Anadenanthera peregrina (red angico), Psidium guajava (guava) and Bixa orellana (annatto). For that, curves of imbibition of the seeds of each species were built and, from these, the moments to interrupt the germination and subsequent drying and rehydration were determined to characterize the loss of desiccation tolerance. All species evaluated showed three-phase pattern of seed imbibition. Seeds of Anadenanthera peregrina and Psidium guajava gradually lost their desiccation tolerance, and with the protrusion of the radicle, the tolerance was totally lost. Bixa orellana seeds showed low desiccation tolerance, regardless of the time or occurrence of imbibition. This low germination may be related to the acquisition of secondary dormancy by the seeds.